Cell-penetrating peptides (CPPs): From delivery of nucleic acids and antigens to transduction of engineered nucleases for application in transgenesis - Rádis-Baptista, Gandhi (2017)
Cell-penetrating peptides (CPPs) have been studied for their capacity to translocate across the lipid membrane of several cell types. In membrane translocation, these peptides can remarkably transport biologically active hydrophilic molecules, such as pharmaceuticals, nucleic acids (DNA and RNA) and even high-molecular-weight proteins, Fig. 3 into the cell cytoplasm and organelles. The development of CPPs as transduction agents includes the modi fi cation of gene and protein expression, the reprogramming and di ff erentiation of induced pluripotent stem cells and the preparation of cellular vaccines. A relatively recent fi eld of CPP application is the transduction of plasmid DNA vectors and CPP-fusion proteins to modify genomes and introduce new traits in cells and organisms. CPP-mediated transduction of components for genome editing is an advantageous alternative to viral DNA vectors. Engineered site-speci fi c nucleases, such as Cre recombinase, ZFN, TALENs and CRISPR associated protein (Cas), have been coupled to CPPs, and the fused proteins have been used to permeate targeted cells and tissues. The functionally active fusion CPP-nucleases subsequently home to the nucleus, incise genomic DNA at speci fi c sites and induce repair and recombination. This review has the objective of discussing CPPs and elucidating the prospective use of CPP-mediated transduction technology, particularly in genome modification and transgenesis